Etiquette for medical students’ email communication with faculty members: a single-institution study - Kim, Do-Hwan (BMC Med Educ, 2016)
BACKGROUND: Email is widely used as a means of communication between faculty members and students in medical education because of its practical and educational advantages. However, because of the distinctive nature of medical education, students’ inappropriate email etiquette may adversely affect their learning as well as faculty members’ perception of them. Little data on medical students’ competency in professional email writing is available; therefore, this study explored the strengths and weaknesses of medical students’ email etiquette and factors that contribute to professional email writing. METHODS: A total of 210 emails from four faculty members at Seoul National University College of Medicine were collected. An evaluation criteria and a scoring rubric were developed based on the various email-writing guidelines. The rubric comprised 10 items, including nine items for evaluation related to the email components and one item for the assessment of global impression of politeness. Three evaluators independently assessed all emails according to the criteria. RESULTS: Students were identified as being 61.0 % male and 52.8 % were in the undergraduate-entry program. The sum of each component score was 62.21 out of 100 and the mean value for global impression was 2.6 out of 4. The results demonstrated that students’ email etiquettes remained low-to-mediocre for most criteria, except for readability and honorifics. Three criteria, salutation (r=0.668), closing (r=0.653), and sign-off (r=0.646), showed a strong positive correlation with the global impression of politeness. Whether a student entered a graduate-entry program or an undergraduate-entry program significantly contributed to professional email writing after other variables were controlled. CONCLUSIONS: Although students in the graduate-entry program demonstrated a relatively superior level of email etiquette, the majority of medical students did not write emails professionally. Educating all medical students in email etiquette may well contribute to the improvement of student–faculty relationships as well as their email writing.